A efetividade dos direitos humanos fundamentais sociais de provimento como uma heterotopia do possível: ativismo judicial e políticas públicas - Martins, Marianne Rios de Souza (2006)
The present research proposes to relate the effectiveness of the Fundamental Rights of 2nd Dimension with Public Policies and Judicial Activism. A research of an interdisciplinary nature involving subjects of Sociology, Philosophy of Law, Political Sciences and Law, was sought in an attempt to unilaterally overcome the theme, interlacing them with Incident themes such as: Public Space, Civil Society, Utopia, Separation of Powers and Discretion. There was an expansion to the theory of the three phases of the evolutionary process of Human Rights, adding a fourth phase, which would be the emancipation of the Fundamental Human Rights of 2nd Dimension. A classification was proposed for Fundamental Social Human Rights, dividing them into Social Rights of Provision and Protection. After this conceptual cut, it was analyzed as the object of study the Fundamental Social Human Rights of Providence. Based on Boaventura de santos, it was concluded that the effectiveness of these rights would be a "heterotopia of the possible". The roles of both civil society and the Public Prosecutor's Office and the Judiciary were analyzed for the effectiveness of Fundamental Social Human Rights. In this sense, the concepts of "reserve of the possible" and "reserve of consistency", the latter being based on Habermas and Haberle, were discussed, the participation of society in the interpretation and application of the law by the Judiciary Power was defended, and the importance of figure of the "amicus curiae" in the Brazilian procedural system. The Public Prosecutor's Office was treated within a new functional perspective within four functional modalities. The Judiciary was defended as a "positive legislator", and it was analyzed which obstacles interfere with the effectiveness of the Human Fundamental Social Controls of Providence.